Idiomatic creativity : a cognitive-linguistic model of idiom-representation and idiom-variation in English - Langlotz, Andreas (Human cognitive processing ;, 2006)
This book revisits the theoretical and psycholinguistic controversies centred around the intriguing nature of idioms and proposes a more systematic cognitive-linguistic model of their grammatical status and use. Whenever speakers vary idioms in actual discourse, they open a linguistic window into idiomatic creativity - the complex cognitive processing and representation of these heterogeneous linguistic constructions. Idiomatic creativity therefore raises two challenging questions: What are the cognitive mechanisms that underlie and shape idiom-representation? How do these mechanisms define th.